Effect of dwell time on creep-fatigue life of a high-Nb TiAl alloy at 750 °C. (December 2015) - Yu, Long; Song, Xiping; You, Li; Jiao, Zehui; Yu, Huichen
Graphical abstract: Abstract: The creep-fatigue life of a cast Ti-45Al-8.0Nb-0.2W-0.2B-0.1Y (at.%) alloy was investigated at 750 °C by the consideration of effective dwell time. The life to failure decreases linearly with the increase of effective dwell time, and decreases exponentially with the increase of minimum creep rate. A linear formula and a power-law formula for the life prediction of creep-fatigue were proposed. Both creep-fatigue life prediction formulae have a good agreement with the experimental data.